448 CHARACTERIZATION OF SECRETED PROTEINS OF NON-O157:H7 ENTEROHEMORRHAGIC ESCHERICHIA COLI SEROTYPES AND THEIR USE IN BOVINE VACCINE STUDIES. (1st January 2006) - Sekirov, I.; Li, Y.; Deng, W.; deHoog, C. L.; Finlay, B. B.
Abstract : Purpose: Secreted proteins (SPs) of enterohemorrhagic Escherichia coli (EHEC), a diarrhegenic pathogen, are central to the infection process, accounting not only for EHEC's ability to invade the host and evade host defense systems but also for many clinical manifestations of the disease. To learn more about EHEC pathogenesis, the SPs of various EHEC human and bovine isolates were studied. Methods: SPs of all serotypes used in the study were analyzed by SDS-PAGE and Western blotting. Additionally, some SPs of EHEC O103:H2 were analyzed by mass spectrometry and sequenced. SPs of 5 common EHEC serotypes were concentrated by ultrafiltration for use in bovine vaccine studies. Results: SPs of non-O157:H7 serotypes were found to be sufficiently dissimilar to prevent their recognition by monoclonal antibodies directed against O157:H7 SPs, with the exception of the SPs of O55:H7. Polyclonal antibodies directed against EHEC O157:H7 SPs detected the SPs of most other serotypes. O103:H2 Z2338 was completely sequenced and found to be 96% identical to O157:H7 Z2338; however, Z2149 of O103:H2, which was partially sequenced, was only 40% identical to its O157:H7 homologue. Both proteins were secreted in greater amounts by O103:H2 than by O157:H7. Western blotting of SP from different EHEC serotypes using sera of 2 convalescent patients from 2 different EHEC outbreaks demonstrated obvious variations in patients' serological responses. SPs of five serotypes commonly implicated in EHEC outbreaks were prepared for future use in bovine vaccine trials. Conclusions: These results demonstrate the heterogeneity of SPs of different EHEC serotypes and highlight the diversity in serotype composition of different EHEC outbreaks. They further our knowledge of EHEC SP arsenal and can play a role in the design of effective bovine and potentially human vaccines against EHEC.